Identification of differential item functioning by race and ethnicity in the Childhood Trauma Questionnaire. (August 2019) - Rodriguez, Violeta J.; Shaffer, Anne; Are, Funlola; Madden, Amber; Jones, Deborah L.; Kumar, Mahendra
Abstract: Background: The accurate assessment of childhood maltreatment (CM) is important in medical and mental health settings given its association to adverse psychological and physical outcomes. Reliable and valid assessment of CM is also of critical importance to research. Due to the potential of measurement bias when comparing CM across racial and ethnic groups, invariant measurement is an important psychometric property of such screening tools. Objective: In this study, differential item function (DIF) by race and ethnicity was tested. Uniform DIF refers to the influence of bias on scores across all levels of childhood maltreatment, and non-uniform DIF refers to bias in favor of one group. Method: Participants were N =1, 319 women and men (Mage =36.77, SDage =10.37) who completed the Child Trauma Questionnaire-Short Form; 42.7% were women, 57.3% were male; 58.9% were White-American, 22.1% Black-American, and 8.0% as other; 26.3% were Hispanic. Results: Using empirical thresholds, non-uniform DIF was identified in five items by race, and no items by ethnicity. Conclusions: Uniform DIF is less problematic given that mathematical corrections can be made to adjust scores for DIF. However, non-uniform DIF can usually only be corrected by removing the DIF items from the scale. Further methodological research is needed to minimize measurement bias to effectively assess racially diverse populations.